Mother-to-child transmission of HIV in Brazil during the years 2000 and 2001: results of a multi-centric study Transmissão vertical do HIV no Brasil em 2000 e 2001: resultados de um estudo multicêntrico - Regina Célia de Menezes Succi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The objective of this study was to assess mother-to-child transmission rates of HIV in Brazil during the years 2000 and 2001, and to identify the maternal and neonatal variables that were associated with this transmission. It was a cross-sectional, observational study with retrospective data obtained from patient medical records. The children were followed at 63 medical sites situated in five geographical macro-regions of the country (20 States and the Federal Capital). Children enrolled were those that were born of HIV-infected mothers and it was necessary for the mothers to present documented proof of HIV-infection before or during pregnancy, at time of delivery or in the first three months after delivery. There were 2,924 children enrolled and mother-to-child transmission rates of HIV were 8.6% (95%CI: 7.2-10.2) for the year 2000 and 7.1% (95%CI: 5.8-8.6) for the year 2001. The following variables were associated with lower mother-to-child transmission rates of HIV: elective cesarean section, diagnosis of mother's infection before or during pregnancy, access to HIV viral load and T CD4+ lymphocyte count during prenatal care, greater birth weight and avoidance of breastfeeding. O objetivo do estudo foi descrever as taxas de transmissão vertical do HIV no Brasil nos anos de 2000 e 2001, e identificar as variáveis maternas e dos recém-nascidos associadas à transmissão. O estudo foi transversal, observacional, com dados retrospectivos obtidos por meio da análise de prontuários médicos em 63 serviços localizados nas cinco macrorregiões geográficas do país (vinte estados e o Distrito Federal). Foram consideradas, para o estudo, crianças nascidas de mães infectadas pelo HIV que apresentaram documentação da infecção pelo vírus antes ou durante a gestação, no momento da admissão para o parto ou nos três primeiros meses após o parto. Foram incluídas 2.924 crianças e a taxa de transmissão vertical do HIV foi: 8,6% em 2000 (IC95%: 7,2-10,2) e 7,1% em 2001 (IC95%: 5,8-8,6). As seguintes variáveis foram associadas com a transmissão vertical do HIV: parto cesárea eletiva, diagnóstico da infecção materna antes ou durante a gestação, acesso a exames de quantificação da carga viral do HIV e contagem de linfócitos-T CD4+ durante a gestação, peso ao nascimento e ausência de aleitamento materno.